Selectivity of insecticides for adult workers of Apis mellifera (Hymenoptera: Apidae) - THOMAZONI, DANIELLE; SORIA, MIGUEL F.; KODAMA, CÁSSIO; CARBONARI, VLADSON; FORTUNATO, RONI P.; DEGRANDE, PAULO E.; VALTER, V. A. Jr. (Revista Colombiana de Entomología, 2009)
Cotton is a crop that is attractive to a wide variety of organisms, including pests, natural enemies of the pests and arthropod pollinators. Consequently, integrated pest management is necessary for this crop as chemical control is often required to avoid production losses. Among pollinators found on cotton, Apis mellifera is one of the most important, as it can increase cotton production 20 – 30%. On the other hand, selectivity is an important characteristic of insecticides, as it makes it possible to lessen impacts on pollinators and other non-target organisms. We examined the toxicity of various insecticides for honey bees foraging on cotton in a greenhouse, including Turbine®  500 WG (150 g ha-1) (flonicamid), Actara®  250 WG (200 g ha-1) (thiamethoxam), Cartap®  500 SP (1500 g ha-1) (cartap), Talstar®  100 CE (1000 mL ha-1) (bifenthrin) and Match®  50 CE (1000 mL ha-1) (lufenuron). Applications of Talstar®, Actara®  and Cartap® were quite toxic. Talstar® was the most deadly, while Match CE® and Turbine® were only slightly toxic for adult honey bees. The Match CE®  treatment mortality was similar to that of the control; thus, we classified it as innocuous for A. mellifera adults.